PENERAPAN TEKNOLOGI INOVATIF DALAM MEDIA PEMBELAJARAN UNTUK MENINGKATKAN PRESTASI SISWA DI SMK PEMBANGUNAN - Ahmad Khusnaeni (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
The use of technology in learning at SMK Pembangunan has shown a significant impact on improving student achievement through various innovations in instructional media. Technology, from online platforms to interactive simulations, has opened up opportunities for more engaging, eflective, and student-centered learning. The impact is not only evident in understanding the material and practical skills but also in students' learning motivation. However, to achieve maximum eflectiveness, continuous development in teacher skills, technology access, and integration of technology into the curriculum are needed. With these measures, it is hoped that SMK Pembangunan can create a dynamic and inclusive learning environment, preparing students to face the challenges of the digital era workforce.